English as a Medium for Digital Da’wah Communication: Challenges and Opportunities in the Global Era - Intan Trine Chodija; Jami’atus Sholeha; Novriyani (Madiha Press, 2026)
The rapid development of digital technology has transformed religious communication, enabling Islamic da’wah to reach audiences beyond geographical and linguistic boundaries. This research examines the use of English as a medium for digital da’wah communication and explores its opportunities and challenges in the global era. A qualitative content analysis was employed to examine four English language digital da’wah contents focusing on patience, helping others, prayer, and peace, and respect. The findings incicate that English functions as a potential linguistic bridge for communicating Islamic values to diverse audiences. The use of accessible vocabulary and universal themes facilitates potential intercultural communication. However, the analysis also reveals challenges related to the translation of Islamic concepts, semantic reduction, cultural interpretation, and religious contextualization. The research concludes that English mediated digital da’wah offers opportunities for broader communication, provided that linguistic accessibility is balanced with religious accuracy and intercultural sensitivity.